STRATEGIC TAX PLANNING AND TECHNOLOGICAL INNOVATION: A COMPREHENSIVE EXAMINATION OF THE INTERPLAY BETWEEN TAX POLICIES, RESEARCH AND DEVELOPMENT (R&D) EXPENDITURES, AND FIRM PERFORMANCE - Aulia Kartika Putri; Evan Andarianto Ammaridho; Rizky Mega Arini; Muhammadong; Mohamad Khairi Bin Haji Othman (CV. Adiba Aisha Amira, 2025)
This comprehensive literature review critically examines the intricate interplay between strategic tax planning, Research and Development (R&D) expenditures, and firm performance. A meticulous synthesis of diverse scholarly contributions highlights the significant impact of tax incentives, such as R&D tax credits and accelerated depreciation, in fostering innovation. The exploration extends to the determinants of R&D spending, encompassing industry characteristics, firm size, and technological intensity, offering a nuanced understanding of the multifaceted nature of corporate decision-making. The broader implications for firm performance, including enhanced competitiveness, improved profitability, and sustained viability, are elucidated. Furthermore, the review underscores the dynamic evolution of tax policies and their implications for corporate behavior, emphasizing the need for adaptability in strategic tax planning. As scholars and practitioners navigate this intricate landscape, the synthesis provides a robust foundation for future research directions. The keywords encapsulate the central themes: strategic tax planning, Research and Development, firm performance, tax incentives, R&D spending, and technological innovation.